DAMPAK PROGRAM SERTIFIKASI TERHADAP PENINGKATAN PROFESIONALISME GURU PADA SMAN 1 GAUNG KABUPATEN INDRAGIRI HILIR - jurnalmap map; Sy. Yuli Andriani (Program Pascasarjana Universitas Wijaya Putra Surabaya, 2020)
This study aims to describe the professionalism of teachers in SMAN 1 Gaung, Indragiri Hilir Regency and to describe the impact of Teacher Certification in Supporting Professionalism of Teachers at SMAN 1 Gaung, Indragiri Hilir Regency. The type of research used is descriptive research with a qualitative approach. In this study the informants were the School Committee, Deputy Principal and teacher representatives. At SMAN 1 Gaung, Indragiri Hilir Regency. From the results of observations, documentation and informants' answers, it is known that the implementation of certification has a major influence on teacher competencies, especially in making lesson plans, preparing instructional media, and planning learning methods. This has a significant impact on teachers in carrying out teaching and learning activities in schools. Keywords: Certification, professionalism